2023
DOI: 10.1021/acs.energyfuels.2c03840
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Verification of Gas-Bearing Parameter Evaluation Methods for Deep Shale Based on the Pressure Coring Technique

Abstract: Gas-bearing properties, such as gas-in-place (GIP) content and adsorbed gas ratio (AGR), have drawn considerable attention because they are essential for shale gas resource evaluation and sweet spot forecasting. The above-mentioned metrics have been determined using a variety of approaches, but they lack systematic comparison and accuracy verification, particularly for deep shale gas, where conventional methods frequently fall short. A total of 30 shales were taken for the investigation utilizing pressure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The USBM method is known for its linear characteristics, while the curve characteristic of lost gas recovered by the CIF model is “convex downward” first and then “convex upward”. In addition, the USBM method takes half of the retrieve time as time zero, whereas the CIF model takes the moment when the reservoir pressure is equal to the environmental pressure (the sum of mud weight and atmospheric pressure) as time zero. ,,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The USBM method is known for its linear characteristics, while the curve characteristic of lost gas recovered by the CIF model is “convex downward” first and then “convex upward”. In addition, the USBM method takes half of the retrieve time as time zero, whereas the CIF model takes the moment when the reservoir pressure is equal to the environmental pressure (the sum of mud weight and atmospheric pressure) as time zero. ,,, …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the USBM method takes half of the retrieve time as time zero, whereas the CIF model takes the moment when the reservoir pressure is equal to the environmental pressure (the sum of mud weight and atmospheric pressure) as time zero. 12,21, 30,57 Using the USBM method, lost gas content ranges 0.74− 2.64 mL/g, averaging 1.53 mL/g, and the GIP content ranges 1.49−4.14 mL/g, averaging 2.69 mL/g. For shale samples from Well JY A, the calculation results of the USBM method are generally lower (Figure 8a).…”
Section: Comparison Between the Cif Model And Usbm Methodmentioning
confidence: 99%
“…On this basis, Li developed an isotope fractionation model considering multiscale and multimechanism coupling, in which the gas equation of state was used for the differential pressure seepage of free gas in fractures, the one-dimensional continuous flow equation coupling diffusion and adsorption/desorption was used for the gas flow in matrix pores, and Fick’s second law was used for the diffusion of dissolved gases in the kerogen pores . This model has been initially applied in Fuling , and Luzhou blocks , in the Sichuan Basin, and good evaluation results have been obtained, and it has been verified by pressure-preserving coring. The accuracy of this model in evaluating the in situ gas content parameters is better than the traditional USBM method, polynomial fitting method, and Amoco method.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have found significant isotopic fractionation during gas desorption from shale and coal beds. The latter further clarified the isotope fractionation characteristics during desorption and revealed the mechanism of isotope fractionation and found that the isotope fractionation characteristics of shale gas desorption were closely correlated with the shale’s composition, physical properties, and gas-bearing properties. Li et al used this as an entry point to develop a set of carbon isotope fractionation (CIF) models for evaluating gas content according to different gas flow mechanisms by calibrating the amount of desorbed gas and isotope values. This model has now been preliminarily applied in Jiaoshiba , and Luzhou shale gas block , in the Sichuan Basin and has achieved better evaluation results, but the applicability and accuracy of this method in normal-pressure shale gas have yet to be verified. Especially, there is a lack of systematic research on analyzing and comparing the evaluation results of gas-bearing parameters in normal-pressure shale reservoirs using multiple methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation